CITRICULTURA AND COOPERATIVE AGRIBUSINESS IN BRAZIL - Zulian, Aline; Dörr, Andréa Cristina; Almeida, Sabrina Cantarelli (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708700 The citrus chain has gained importance in Brazilian agribusiness with market expansion and improvement activity. Brazil is highlighted in orange production and export of fruit juice. Considering that the citrus industry as well as other agricultural activities, involves processing of fruits, this activity requires greater investment and industrialization. Thus, the system of citrus agribusiness encompasses many procedures, and cooperatives and associations are forms of economic organizations that often enable the development of small farmers and provide ways to insert themselves in the competitive market. This study seeks to make a panorama of citrus, with a focus on orange and tangerine, and describe the importance of agribusiness cooperative. Thus, we conclude that the citrus sector has great importance for the Brazilian agribusiness and the presence of a cooperative may be a favorable factor for the growth of small producers.